2021
DOI: 10.1155/2021/7721760
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine in Schizophrenia: Independent Pathogenetic Factor with Prooxidant Activity or Integral Marker of Other Biochemical Disturbances?

Abstract: A wide range of studies have demonstrated that hyperhomocysteinemia is associated with the risk of schizophrenia, but currently available assumptions about the direct involvement of homocysteine (Hcy) in the pathogenesis of schizophrenia are hypothetical. It is possible that in vivo Hcy is only a marker of folate metabolism disturbances (which are involved in methylation processes) and is not a pathogenetic factor per se. Only one study has been conducted in which associations of hyperhomocysteinemia with oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…32 Impaired folic acid and vitamin B12 levels are the main contributors to OCM changes. 33 The present study findings show significantly elevated CRP level within the schizophrenia inpatient group consistent with a published study by Dickerson et al among schizophrenic patients. In Dickerson et al's study, schizophrenia patients received the following medications: atypical antipsychotics (clozapine, risperidone, olanzapine), antidepressant medication, anti-cholinergic, and lithium.…”
supporting
confidence: 93%
“…32 Impaired folic acid and vitamin B12 levels are the main contributors to OCM changes. 33 The present study findings show significantly elevated CRP level within the schizophrenia inpatient group consistent with a published study by Dickerson et al among schizophrenic patients. In Dickerson et al's study, schizophrenia patients received the following medications: atypical antipsychotics (clozapine, risperidone, olanzapine), antidepressant medication, anti-cholinergic, and lithium.…”
supporting
confidence: 93%
“…There is also increasing evidence that Hcy is directly or indirectly involved in multiple pathways in pathophysiological mechanisms of schizophrenia. Methylation pathway defects (including catecholamine methylation) due to folate and cobalamin deficiencies, and impaired re-methylation of methionine by Hcy, can cause hyperhomocysteinemia [ 36 ]. Another impaired pathway is transsulfuration pathway, which is a metabolic pathway from Hcy to L-cysteine to glutathione (GSH), resulting in reduced GSH levels and oxidative phosphorylation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Zhilyaeva et al have observed that PANSS negative symptom scores, including difficulty with abstract thinking, lack of spontaneity and fluency in conversation, stereotyped thinking, and motor retardation, were more pronounced in SP patients with elevated Hcy levels, supporting the positive association between PANSS and high Hcy levels that we observed. 24,25 It has been also evaluated that patients with SP perform worse on cognitive assessments, and high levels of Hcy are associated with this. [26][27][28] Some articles have shown an association between elevated Hcy levels and cognitive dysfunction in patients with SP.…”
Section: Discussionmentioning
confidence: 99%